Repair and mutagenesis of the genome of a deletion mutant of the coronavirus mouse hepatitis virus by targeted RNA recombination. - Koetzner, C A (1992)
The genetic characterization of a nucleocapsid (N) protein mutant of the coronavirus mouse hepatitis virus (MHV) is described. The mutant, Albany 4 (Alb4), is both temperature sensitive and thermolabile. Analysis of the progeny of a mixed infection showed that the defective Alb4 allele is recessive to wild type, and its gene product is diffusible. The N protein of Alb4 was found to be smaller than its wild-type counterpart, and sequence analysis of the Alb4 N gene revealed that it contains an internal deletion of 87 nucleotides, producing an in-frame deletion of 29 amino acids. All of these properties of Alb4 made it ideal for use as a recipient in a targeted RNA recombination experiment in which the deletion in Alb4 was repaired by recombination with synthetic RNA7, the smallest MHV subgenomic mRNA. Progeny from a cotransfection of Alb4 genomic RNA and synthetic RNA7 were selected for thermal stability. Polymerase chain reaction analysis of candidate recombinants showed that they had regained the material that is deleted in the Alb4 mutant. They also had acquired a five-nucleotide insertion in the 3' untranslated region, which had been incorporated into the synthetic RNA7 as a molecular tag. The presence of the tag was directly verified, as well, by sequencing the genomic RNA of purified recombinant viruses. This provided a clear genetic proof that the Alb4 phenotype was due to the observed deletion in the N gene. In addition, these results demonstrated that it is possible to obtain stable, independently replicating progeny from recombination between coronavirus genomic RNA and a tailored, synthetic RNA species.